ISTILAH-ISTILAH MAKANAN DAN MINUMAN DALAM BAHASA INGGRIS DAN BAHASA TONTEMBOAN (SUATU ANALISIS KONTRASTIF) - Sekeon, Jennifer Elisa; Pamantung, Rina P.; Lotulung, Donald R. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
Â ABSTRACTÂ This research is entitled â€œTerms of Food and Beverage in English and Tontemboan Language (A Contrastive Analysis)â€. The objectives of this research are to find out, classify, analyze and describe the kinds of food and beverage, the way food and beverage are made and the basic ingredients of food and beverage in English and Tontemboan Language and to find out the similarities and differences in both languages. This research uses a descriptive method. The data of food and beverage in English were collected from skripsi, book, and article, while in Tontemboan Language were collected from informants and also by taking picture of foods and beverages in some wedding party, sorrow ceremony, restaurant, and traditional market. The data that have been collected then analyzed by using Frisch in Hickersonâ€™s and Foleyâ€™s theories and then the writer uses Ladoâ€™s theory to make a contastive analysis in finding out the similarities and differences of both language. The result shows that the kind of terms of food in English consist of two groups, those are solid foods and beverages. Solid food consist of meat, bread, fruits, vegetables, fish and sea food. Beverages/drinks consist of alcoholic and non-alcoholic drink. Tontemboan language consist of three groups, those are solid foods, liquid foods, and beverages. Solid food consist of meat, bread, fruits, vegetables, fish and rice. Liquid foods consist of rice, vegetables, and fruits. Beverages/drinks consist of alcoholic and non-alcoholic drink. English food and beverage based on the way food and beverage are made: baking, grilling, sauteing, boiling, steaming, blending and squeeze, while in Tontemboan language namely tare/panggang (grilling), tumis (sauteing), goreng (frying), kukus (steaming), bakar (smoking), and rebus (boiling). Food and beverage based on the basic ingredients are meat, fish, wheat, flour, fruits, vegetables, milk, coffee, and herbal plants, while in Tontemboan language are daging (meat), ikan (fish), sayur-sayuran (vegetables), buah-buahan (fruits), umbi-umbian (tubers) tepung (flour), beras (rice), kacang (nut), kopi (coffee), air nira (nira water) and daun (leaf). The kind of terms of food and beverage in English and Tontemboan language have the same categories, namely solid food and beverage. English and Tontemboan language have same way food and beverage are made, those are grilling, sauteing, steaming, and boilling. English and Tontemboan language have same basic ingredients, those are meat, fish, flour, fruits, vegetables, and coffee. The differences in categories Tontemboan has liquid foods, but in English has not. The kind of food in English has bread, but in Tontemboan Language has not. In the way of food and beverage are made, Tontemboan language has frying but in English has not. In the basic ingredient, English has wheat while in Tontemboan language has rice.Keywords: Terms of Food and Beverage, English and Tontemboan Language, Contrastive Analysis